Development of a Novel Gastrointestinal Endoscopic Robot Enabling Complete Remote Control of All Operations: Endoscopic Therapeutic Robot System (ETRS). (4th November 2019) - Kume, Keiichiro; Sakai, Nobuo; Ueda, Toru
Abstract : Background and Objective . The master and slave transluminal endoscopic robot and other flexible endoscopy platforms are designed primarily for the remote control of forceps, with manipulation of the endoscope itself still dependent on conventional techniques. We have developed an endoscopic therapeutic robot system (ETRS) that provides complete remote control of all forceps and endoscope operations. Method . We carried out endoscopic submucosal dissection (ESD) in porcine stomachs using the ETRS. All procedures were completed with the endoscopist seated at the console the entire time. Results . Total en bloc resection was achieved in all 7 cases with no complications. The mean total procedure time was 36.14 ± 14.98   min, the mean size of the resected specimen was 3.39 ± 0.66   cm × 3.03 ± 0.63   cm, and the mean dissection time was 14.91 ± 8.61   min . Conclusion . We successfully used the ETRS to perform completely remote-controlled ESD in porcine stomachs.